A Dual-Wideband Balanced Bandpass Filter Based on Branch-Line Structure With Controllable Common-Mode Suppression - Ren, Baoping; Liu, Xinlei; Guan, Xuehui; Xu, Mengrou; Zhang, Zhi-Chong (Frontiers in Physics, 2021)
In this paper, a novel dual-wideband balanced bandpass filter (BPF) based on branch-line structure is proposed. For analysis, the equivalent circuits of differential-mode (DM) and common-mode (CM) of the filter are built based on the even- and odd-mode method. With a proper synthesis design of DM bisection, dual passbands with a multi-order filtering response can be obtained. Additionally, three open-circuited stubs are centrally loaded on the CM bisection and six controllable transmission zeros are therefore generated. Thus, two stopbands are formed and then a favorable CM suppression within DM passbands is obtained. For demonstration, a third-order dual-wideband balanced BPF is designed with two passbands operating at 2.54 GHz and 4.62 GHz. Good agreement between the simulated results and measured results is obtained, which verifies the validity of the proposed design method.